Dose-dependent renoprotective effects of sacubitril/valsartan in heart failure: a retrospective study - Takahiro Kato; Yusuke Nakano; Noriko Yasukawa; Masafumi Oonishi; Yukihiro Hamada (Renal Failure)
To evaluate the dose-dependent renoprotective effects of sacubitril/valsartan in heart failure patients. This retrospective observational study included patients with heart failure (Stage B or higher, B-type natriuretic peptide (BNP) >100 pg/mL or N-terminal proBNP >300 pg/mL) who initiated sacubitril/valsartan (SV) treatment. Patients were classified by final SV daily dose (50, 100, 200, or 400 mg) at 18 months. Factors associated with eGFR changes were identified using multiple regression analysis. A total of 157 patients (mean age 74.8–77.9 years, 64.3% male) were stratified by daily SV dosage groups (50 mg, n = 20; 100 mg, n = 46; 200 mg, n = 62; 400 mg, n = 29). Baseline characteristics were similar across groups for eGFR, heart failure stage, diabetes history, myocardial infarction, atrial fibrillation, proteinuria, and use of most heart failure medications. However, hypertension prevalence and systolic blood pressure differed significantly between groups (p < 0.05). One-way ANOVA revealed significant dose-dependent differences in eGFR changes among SV dosage groups (p < 0.05). In the final multiple linear regression model, SV dosage (p < 0.05) was a significant factor associated with eGFR changes, with proteinuria showing a trend toward significance. Sex and BNP levels ≥400 pg/dL were not significant. Sensitivity analysis converting SV dosage to a categorical variable confirmed these findings. Stratification by proteinuria status demonstrated dose-dependent relationships in both proteinuria-positive and proteinuria-negative subgroups, with more pronounced dose dependency in the proteinuria-positive group (p < 0.001). SV exhibits dose-dependent renoprotective effects in heart failure patients. Optimizing SV dosage may be beneficial for heart failure patients with concurrent kidney dysfunction, especially those with proteinuria.